Anti-Inflammatory Properties of Diclofenac Sodium on Background of Its Combined Use With Cryopreserved Placenta Extract in Experiment - Hladkykh, Fedir (Problems of Cryobiology and Cryomedicine, 2021)
Probl Cryobiol Cryomed 2021; 31(4): 364–367